(untitled) (World Bulletin of Education and Learning, 2025)
The mentor–apprentice system plays a crucial role in enhancing the professional formation of future specialists in higher education. As universities shift toward competency-based education, effective collaboration between experienced mentors and novice learners has become essential for bridging theoretical knowledge with real-world practice. This article examines the pedagogical value of mentor–apprentice relations in fostering professional competencies among university students, focusing on communicative ability, critical thinking, practical skills, professional ethics, and independent decision-making. The study highlights how personalized guidance, motivational support, and continuous feedback contribute to students’ adaptability in dynamic professional environments. It also emphasizes the integration of traditional mentorship culture with modern pedagogical innovations such as digital communication, reflective practice, and collaborative learning models. The effectiveness of mentorship depends on structured planning, institutional support, and the active participation of both mentors and learners. The findings reveal that a well-organized mentor–apprentice system enhances academic success, improves practical skills acquisition, and supports the social and emotional development of students. Recommendations are proposed for strengthening mentorship programs through professional development, student engagement strategies, and continuous assessment of learning outcomes within higher education institutions.